2017
DOI: 10.1080/13811118.2017.1358223
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions of Self-Harm: Perceived Motivations of (and Willingness to Help in Response to) Adolescent Self-Harm

Abstract: We investigated public perceptions of, and responses to, adolescent self-harm-an under-researched topic, given that the majority of self-harm in this group is not disclosed to formal support services. Participants (N = 355, aged 18-67 years) were presented with 1 of 10 vignettes and completed self-report measures assessing perceived motivations for self-harm and helping/rejecting responses. Vignettes were manipulated across conditions for stated motivation, controllability of stated cause, and presentation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The complexity of the relationship between BD and SUD is reflected in the relationship between mania, biological sex, and SUD; males with a higher occurence rate of mania are more likely to experience SUD 74 . There are many overt behaviors that are driven in part by internal motivations, they include eating disorders, compulsive gambling, and other behaviors leading to self‐harm 75 . While it can be argued that disease causes behavior, and behavior can cause disease, these concepts are clearly not interchangeable and should be evaluated independently, as well as in the context of associated phenomena.…”
Section: Clinical and Phenomenological Basis For Bdmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of the relationship between BD and SUD is reflected in the relationship between mania, biological sex, and SUD; males with a higher occurence rate of mania are more likely to experience SUD 74 . There are many overt behaviors that are driven in part by internal motivations, they include eating disorders, compulsive gambling, and other behaviors leading to self‐harm 75 . While it can be argued that disease causes behavior, and behavior can cause disease, these concepts are clearly not interchangeable and should be evaluated independently, as well as in the context of associated phenomena.…”
Section: Clinical and Phenomenological Basis For Bdmentioning
confidence: 99%
“…74 There are many overt behaviors that are driven in part by internal motivations, they include eating disorders, compulsive gambling, and other behaviors leading to self-harm. 75 While it can be argued that disease causes behavior, and behavior can cause disease, these concepts are clearly not interchangeable and should be evaluated independently, as well as in the context of associated phenomena.…”
Section: Motivated Behaviors Subclassmentioning
confidence: 99%
“…A recent study by Nielsen and Townsend (2018), which incorporated vignettes to ask adults how they would respond to a NSSI disclosure, identified significant differences in individual responses based on the perceived motivations of a person's NSSI. More specifically, community samples reported they were more likely to endorse rejecting behaviours (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Although direct comparisons cannot be made, discrepancies were identified between the responses as perceived by those who disclosed their NSSI and responses as reported by those who received the disclosure. In particular, recipients of NSSI disclosure had a greater tendency to report that they did or would provide support, which is evident in that four of the six studies reported some type of supportive response (Bresin et al, 2013; Law et al, 2009; Mackay & Barrowclough, 2005; Nielsen & Townsend, 2018). Another key finding was that the recipients' responses to NSSI disclosure were circumstantial, depending on the perceived motivation and the controllability of the event preceding NSSI.…”
Section: Discussionmentioning
confidence: 99%
“…These options were adapted from the "helping scenario", posited by Nielsen and Townsend (2018, p. 485) and used to assess young people's spontaneous reactions to self-injury. Responses to this item were reverse coded and adjusted to the 7-point system for interpretability, with higher scores indicating higher endorsement of favorable (helping) reactions towards the peer's character (Nielsen & Townsend, 2018). The internal consistency estimates of Cronbach's α were .71 for items 1-3 which can explain participants' evaluation of the peers' NSSI and .79 for items 4-6 in regards to the attitude and response that participants felt willing to show to the self-injuring peer characters.…”
Section: Indicators Of the Reactions To Nssimentioning
confidence: 99%